1990
DOI: 10.1016/0735-1097(90)90188-u
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of coronary hemodynamics in patients with internal mammary artery and saphenous vein coronary artery bypass grafts: A noninvasive approach using combined two-dimensional and Doppler echocardiography

Abstract: Blood flow in bypass grafts and recipient left anterior descending coronary arteries was evaluated with combined two-dimensional and Doppler echocardiography in 15 patients with an internal mammary artery graft and in 24 patients with a saphenous vein graft. Comparative studies of coronary hemodynamics were also performed regarding these two different grafting techniques. The graft vessel was detected in 11 (79%) of 14 patients with an internal mammary artery graft and in 20 (87%) of 23 with a saphenous vein g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
4

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(28 citation statements)
references
References 13 publications
2
22
0
4
Order By: Relevance
“…Graft flow velocity was characterized by a biphasic pattern, with one peak in systole and a second peak in diastole. Similar findings have been obtained using invasive Doppler guidewire approaches and transthoracic Doppler echocardiography (7,14). MRI-assessed volume flow of grafts with three sequential anastomoses significantly differed from single grafts.…”
Section: Mr Quantification Of Graft Flow and Flow Reservesupporting
confidence: 72%
See 1 more Smart Citation
“…Graft flow velocity was characterized by a biphasic pattern, with one peak in systole and a second peak in diastole. Similar findings have been obtained using invasive Doppler guidewire approaches and transthoracic Doppler echocardiography (7,14). MRI-assessed volume flow of grafts with three sequential anastomoses significantly differed from single grafts.…”
Section: Mr Quantification Of Graft Flow and Flow Reservesupporting
confidence: 72%
“…Two-dimensional (2D) Doppler echocardiography is restricted to evaluation of grafts placed on the left anterior descending coronary artery (14)(15)(16). A unique feature of MRI is that, in addition to standard imaging of morphology, blood flow can be quantified within the grafts.…”
Section: Imaging Modalities Capable Of Evaluating Graftsmentioning
confidence: 99%
“…Indeed, in situ LITA is a resistance conduit with a prevalent systolic flow, but after CABG it is attached to a low resistance vascular bed characterized by prevalent diastolic flow. 17 The increased flow 18 leads to higher peak and time-averaged flow velocities 17 and thus to higher shear stress, known to favor NO production. 19 Moreover, a high intrinsic production of NO in the LITA has already been described.…”
Section: Discussionmentioning
confidence: 99%
“…Pulsed Doppler echocardiography was first reported in the 1970s as a useful method of assessing the patency of saphenous vein coronary bypass grafts, 18,19 and other reports [1][2][3] demonstrated that LITA graft flow could be detected by transthoracic echocardiography with a parasternal or supraclavicular approach, although the detection rate was unsatisfactory. Recent studies have demonstrated that high-frequency transthoracic echocardiography can detect significant stenosis of the LITA graft by evaluating the ratio of the diastolic-to-systolic velocity or the diastolic fraction of the LITA graft flow; [4][5][6] however, the flow pattern is influenced by other factors, such as the site of measurement within the LITA graft, the persistence of the branches of the LITA, the degree of stenosis in the native coronary artery and the regional wall motion of the left ventricle.…”
Section: Previous Studiesmentioning
confidence: 99%